Features of Public Budgeting and Control in Australia (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The Australian Accounting Standards Board and the formation of budgetary control. Australian Accounting Standards Board (AASB) for accounting standards for both the private and public sectors is the responsible body.Australian Accounting Standards (AAS) are consistent with IFRS and IPSAS, except for specific additional requirements applicable in Australia. There are currently 54 standards, 17 of which are dual standards for commercial and non-commercial organizations.